Urological complication following aortoiliac graft: case report and review of the literature - Borges, Leonardo Lima; Torricelli, Fábio César Miranda; Ebaid, Gustavo Xavier; Lucon, Antônio Marmo; Srougi, Miguel (São Paulo Medical Journal, 2010)
CONTEXT: Ureteral stenosis and ureterohydronephrosis may be serious complications of aortoiliac or aortofemoral reconstructive surgery. CASE REPORT: A 62-year-old female patient presented with a six-month history of left lumbar pain. She was a smoker, and had mild chronic arterial hypertension and Takayasu arteritis. She had previously undergone three vascular interventions. In two procedures, Dacron prostheses were necessary. Excretory urography showed moderate left ureterohydronephrosis and revealed a filling defect in the ureter close to where the iliac vessels cross. This finding was compatible with ureteral stenosis, and the aortoiliac graft may have been the reason for this inflammatory process. The patient underwent laparotomy, which showed that there was a relationship between the ureteral stenosis and the vascular prosthesis. Segmental ureterectomy and end-to-end ureteroplasty with the ureter crossing over the prosthesis anteriorly were performed. There were no complications. The early and late postoperative periods were uneventful. The patient evolved well and the results from a new excretory urogram were normal. We concluded that symptomatic ureterohydronephrosis following aortoiliac graft is a real complication and needs to be quickly diagnosed and treated by urologists.